How Warm-Glow, Economic, Environmental, and Health Motives Influence Farmers’ Satisfaction in Practicing Organic Farming in Java, Indonesia - Muntoro; Irham, Irham; Mulyo, Jangkung Handoyo; Suryantini, Any (AGRARIS: Journal of Agribusiness and Rural Development Research, 2024)
Numerous studies have been conducted on organic farming motives, however, less focus has been directed to warm-glow motives—the novelty of this study. This study aims to elaborate on the impact of the warm glow in addition to economic, environmental, and health motives on farmers’ satisfaction in practicing organic farming. This study was conducted in Sleman Regency of Yogyakarta Province as well as Magelang and Semarang Regencies of Central Java Province, Indonesia. By using a structured questionnaire, 259 certified organic farmers were interviewed. A 5-point Likert scale from strongly disagree to strongly agree was employed. A structural equation model (SEM) was utilized to analyze the relationship between the four motives and their influences on farmers’ satisfaction in practicing organic farming. The results revealed that warm-glow motives demonstrated a significant positive effect on the satisfaction of farmers in practicing organic farming concurrently with economic, health, and environmental motives. The significant effect of warm-glow motives has provided a new perspective in understanding their role in organic farming. The study discovered that warm-glow motives corresponded to the noble values of local society and were suitable for developing the organic farming system. The study also disclosed that by encouraging warm-glow motives, farmers could enhance their satisfaction by achieving their goals in economic, health, and environmental aspects. In other words, improving farmers’ satisfaction in organic farming by reinforcing their warm-glow motives was crucial.